2009
DOI: 10.1182/blood-2008-05-156943
|View full text |Cite
|
Sign up to set email alerts
|

Expression of sprouty2 inhibits B-cell proliferation and is epigenetically silenced in mouse and human B-cell lymphomas

Abstract: B-cell lymphoma is the most common immune system malignancy. TCL1 transgenic mice (TCL1-tg), in which TCL1 is ectopically expressed in mature lymphocytes, develop multiple B-and T-cell leukemia and lymphoma subtypes, supporting an oncogenic role for TCL1 that probably involves AKT and MAPK-ERK signaling pathway augmentation. Additional, largely unknown genetic and epigenetic alterations cooperate with TCL1 during lymphoma progression. We examined DNA methylation patterns in TCL1-tg Bcell tumors to discover tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
49
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 58 publications
(92 reference statements)
6
49
0
Order By: Relevance
“…This contrasts with the proposed tumour suppressor activity of SPRY2 in breast, prostate and lung cancer on the basis of its decreased expression, as compared with normal tissue (McKie et al, 2005;Fong et al, 2006;Lo et al, 2006;Sa´nchez et al, 2008;Frank et al, 2009). Concordantly with our results, a meta-analysis of data available at the Oncomine database supports that SPRY2 expression is higher in colon …”
Section: Mutual Regulation Of Sprouty-2 and E-cadherinsupporting
confidence: 78%
See 1 more Smart Citation
“…This contrasts with the proposed tumour suppressor activity of SPRY2 in breast, prostate and lung cancer on the basis of its decreased expression, as compared with normal tissue (McKie et al, 2005;Fong et al, 2006;Lo et al, 2006;Sa´nchez et al, 2008;Frank et al, 2009). Concordantly with our results, a meta-analysis of data available at the Oncomine database supports that SPRY2 expression is higher in colon …”
Section: Mutual Regulation Of Sprouty-2 and E-cadherinsupporting
confidence: 78%
“…SPRY2 expression in human cancers depends on tumour type. SPRY2 is downregulated in breast, prostate, and liver tumours and in B-cell diffuse lymphoma, which would suggest a tumour suppressive role (McKie et al, 2005;Fong et al, 2006;Lo et al, 2006;Sa´nchez et al, 2008;Frank et al, 2009). In contrast, SPRY2 is upregulated in melanoma cell lines concomitantly to mutation of N-RAS and B-RAF (Tsavachidou et al, 2004;Bloethner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Spry1 and Spry2 levels are decreased in prostate and breast cancer, 3,4 whereas the downregulation of Spry2 has been described in hepatocellular carcinoma, B-cell lymphoma or endometrial carcinoma, among others. [5][6][7] Epigenetic silencing 3,5 or loss of heterozygosity 3 are the most widely observed molecular alterations of the Spry genes in tumoral tissue.In this work, we show that Spry1 null mice exhibit overgrowth of the thyroid gland owing to increased proliferation of thyrocytes. Surprisingly, such increase in cell proliferation does not correlate with either elevation of systemic TSH levels or increased activation of the ERK MAPK pathway.…”
mentioning
confidence: 99%
“…Thus, Spry1 and Spry2 levels are decreased in prostate and breast cancer, 3,4 whereas the downregulation of Spry2 has been described in hepatocellular carcinoma, B-cell lymphoma or endometrial carcinoma, among others. [5][6][7] Epigenetic silencing 3,5 or loss of heterozygosity 3 are the most widely observed molecular alterations of the Spry genes in tumoral tissue.…”
mentioning
confidence: 99%
“…This observation confirms that this variant is extremely rare/private. A direct analysis of the SPRY2 cDNA extracted from the LCLs confirmed that this gene is expressed in B cells 14 and the T355 allele is present in transcripts from LCLII7 (data not shown). The same finding was obtained on RNA freshly extracted from white blood cells from individuals II-10, II-7, III-24 and III-26 (data not shown).…”
Section: Exome Sequencing and Bioinformatics Analysismentioning
confidence: 88%